Penyelesaian Perkara Pidana Melalui Majelis Adat Dayak Suruk Di Desa Nanga Tubuk Kabupaten Kapuas Hulu - Anshari Anshari; M. Fajrin; Paskalia Nawa (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2023)
The Dayak Suruk tribe in the Customary Law Community environment in Nanga Tubuk Village, Kapuas Hulu Regency currently still exists, carrying out their ancestral civilization from generation to generation, as the resolution of cases or problems that occur in indigenous communities can be resolved through two possibilities. First, customary law settlements carried out by the community are recognized and legalized by state law through the courts. Second, the case is considered closed and State law does not touch the case. As one of the components of legal substance, the existence of customary law should be given a reasonable place to develop customary law material in accordance with the socio-cultural diversity of society. Based on this, the problem that will be studied further is to find out how criminal cases are resolved through the Dayak Suruk traditional council in Nanga Tubuk Village, Kapuas Hulu Regency, which will be studied further through sociological or socio-legal research. Based on the research results, it is known that customary criminal law is recognized as a source of law in deciding criminal cases by judges. In addition, traditional institutions that impose customary crimes are also recognized in the Indonesian justice system, so that if a case is resolved in a traditional institution then the case is considered if it turns out it is not finished, then it goes to the national court. The imposition of customary punishment or waiting (sanctions) on perpetrators is based on standard standards or guidelines in handling each customary case as stated in the customary deliberation (Musdat).